The Scorch trials - Dashner, James, 1972- (New York : Ember, 2011)
Thomas and the Gladers, having solved the Maze, plan on returning to their lives, but instead find the earth a wasteland with Cranks roaming the desert in search of their next meal and they are faced with the challenge of crossing the Scorch in two weeks in order to arrive at a safe haven.
Sequel to: The maze runner.
Booklist
Horn Book
School Library Journal
Booklist, January 2011
Horn Book, May 2011
Keywords: Science -- Experiments -- Juvenile fiction; Survival -- Juvenile fiction; Science fiction; Science -- Experiments -- Fiction; Survival -- Fiction; Science fiction; Science -- Experiments -- Fiction; Survival skills -- Fiction; Science fiction